Television in Transition in East Asia - Kwak, Ki-Sung (Routledge, 2018)
This book examines the development of television broadcasting in Japan, Hong Kong and South Korea. It explores the policy regimes guiding the development of television broadcasting as a powerful institution and the extent to which new forms of television have become part of each country’s contemporary media mix. It analyses the interests involved in key policy decisions, the institutional dynamics promoting or inhibiting new media markets, and the relative importance in the different countries of cable, satellite, digital broadcasting, and the use of the Internet for purposes associated with television broadcasting. The nature of television regimes in each of the three countries is very different, and the contrasting situations provide great insights into how television is developing, and how it could develop further, both in East Asia and worldwide.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Japon (corpus analysé); _Nettoyé

Civil Society as the Fifth Estate: Civil Society, Media Reform and Democracy in Korea - Kwak, Ki-Sung (Television, Regulation and Civil Society in Asia, 2002)
Since the Korean War (1950-53), South Korea (hereafter Korea) has undergone a series of political changes. The move towards democratisation was largely spurred on by the demonstrations and riots occurring throughout the 1980s. In 1987 massive demonstrations forced the then President Chun DooHwan to call a new presidential election, and President-elect Rho Tae-Woo to implement more social reforms. The notion of civil society in Korea has been a relatively new concept until very recently, mainly because it has not achieved wide recognition from the public, media or the state. The development of a people’s movement advocating democracy could be said to be the foundation of ‘civil society’ in Korea.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé